National trends and outcomes of heart‐kidney transplantation using hepatitis C positive donors. Issue 4 (3rd February 2022) - Diaz‐Castrillon, Carlos E.; Huckaby, Lauren V.; Witer, Lucas; Pope, Nicolas H.; Katz, Marc R.; Baliga, Prabhakar K.; Kilic, Arman
Abstract: Background: This study evaluated the outcomes of combined heart‐kidney transplantation in the United States using hepatitis C positive (HCV+) donors. Methods: Adults undergoing combined heart‐kidney transplantation from 2015 to 2020 were identified in the United Network for Organ Sharing registry. Patients were stratified by donor HCV status. Kaplan‐Meier curves with multivariable Cox regression models were used for risk‐adjustment in a propensity‐matched cohort. Results: A total of 950 patients underwent heart‐kidney transplantation of which 7.8% (n = 75) used HCV+ donors; 68% (n = 51) were viremic and 32% (n = 24) were non‐viremic donors. Unadjusted 1‐year recipient survival was similar between HCV+ versus HCV‐ donors (84% vs 88%, respectively; P  = .33). Risk‐adjusted analysis in the propensity‐matched cohort showed HCV+ donor use did not confer increased risk of 1‐year mortality (hazard ratio .63, 95% CI .17‐2.32; P  = .49). Sub‐group analysis showed viremic and non‐viremic HCV+ donors had similar 1‐year survival as well (84% vs 84%; P  = .95). Conclusions: Compared with recipients of HCV‐ donor dual heart‐kidney transplants, recipients of HCV+ organs had comparable 1‐year survival and clinical outcomes after combined transplantation. Although future studies should evaluate other outcomes related to HCV+ donor use, this practice appears safe and should be expanded further in the heart‐kidney transplant population.